Antiarrhythmic Drug Dosing in Children-Review of the Literature - Nathalie Oeffl; Lukas Schober; Patrick Faudon; Sabrina Schweintzger; Martin Manninger; Martin Köstenberger; Hannes Sallmon; Daniel Scherr; Stefan Kurath-Koller (MDPI AG, 2023)
Antiarrhythmic drugs represent a mainstay of pediatric arrhythmia treatment. However, official guidelines and consensus documents on this topic remain scarce. There are rather uniform recommendations for some medications (including adenosine, amiodarone, and esmolol), while there are only very broad dosage recommendations for others (such as sotalol or digoxin). To prevent potential uncertainties and even mistakes with regard to dosing, we summarized the published dosage recommendations for antiarrhythmic drugs in children. Because of the wide variations in availability, regulatory approval, and experience, we encourage centers to develop their own specific protocols for pediatric antiarrhythmic drug therapy.